Germline BAP1 Mutation in a Family With Multi-Generational Meningioma With Rhabdoid Features: A Case Series and Literature Review - Prasad, Rahul N.; Gardner, Ulysses G.; Yaney, Alexander; Prevedello, Daniel M.; Koboldt, Daniel C.; Thomas, Diana L.; Mardis, Elaine R.; Palmer, Joshua D. (Frontiers in Oncology, 2021)
Meningioma is the most common primary brain tumor, and recurrence risk increases with increasing WHO Grade from I to III. Rhabdoid meningiomas are a subset of WHO Grade III tumors with rhabdoid cells, a high proliferation index, and other malignant features that follow an aggressive clinical course. Some meningiomas with rhabdoid features either only focally or without other malignant features are classified as lower grade yet still recur early. Recently, inactivating mutations in the tumor suppressor gene BAP1 have been associated with poorer prognosis in rhabdoid meningioma and meningioma with rhabdoid features, and germline mutations have been linked to a hereditary tumor predisposition syndrome (TPDS) predisposing patients primarily to melanoma and mesothelioma. We present the first report of a familial BAP1 inactivating mutation identified after multiple generations of a family presented with meningiomas with rhabdoid features instead of with previously described BAP1 loss-associated malignancies. A 24-year-old female presented with a Grade II meningioma with rhabdoid and papillary features treated with subtotal resection, adjuvant external beam radiation therapy, and salvage gamma knife radiosurgery six years later. Around that time, her mother presented with a meningioma with rhabdoid and papillary features managed with resection and adjuvant radiation therapy. Germline testing was positive for a pathogenic BAP1 mutation in both patients. Sequencing of both tumors demonstrated biallelic BAP1 inactivation via the combination of germline BAP1 mutation and either loss of heterozygosity or somatic mutation. No additional mutations implicated in oncogenesis were noted from either patient’s germline or tumor sequencing, suggesting that the inactivation of BAP1 was responsible for pathogenesis. These cases demonstrate the importance of routine BAP1 tumor testing in meningioma with rhabdoid features regardless of grade, germline testing for patients with BAP1 inactivated tumors, and tailored cancer screening in this population.